Pengaruh Leverage dan Keputusan Investasi terhadap Profitabilitas pada PT Aneka Tambang Tbk Periode 2015 - 2024 - Pipih Apiliani; Asep Muhammad Lutfi (Pajak dan Manajemen Keuangan, 2026)
This study aims to determine the effect of Leverage and Investment Decisions on Profitability at PT Aneka Tambang Tbk for the 2015-2024 period, both partially and simultaneously. This research method uses quantitative with a asosiatif research type. Secondary data obtained comes from the Indonesia Stock Exchange website (www.web.idx.com) and the PT Aneka Tambang Tbk website. The results of this study show that the Leverage variable has a t count of -3.166 > t table 2.365 with a significant value of 0.016 < 0.05, so it can be concluded that the Leverage variable (X1) has a significant effect on Profitability (Y). The Investment Decision variable has a t count of -0.673 < 2.365 and with a significance level of the Investment Decision variable of 0.522 > 0.05, it can be concluded that the Investment Decision variable (X2) does not have a significant effect on Profitability (Y). And the results of the F Test obtained an Fcount value of 6.726 > Ftable 4.737 and a significant value of 0.023 < 0.05, meaning that the Leverage and Investment Decision variables together have a significant effect on Profitability. Therefore, the Leverage (X1) and Investment Decision (X2) variables together have a significant effect on the stock price of PT Aneka Tambang Tbk.